An open source LoRa based vehicle tracking system - Norhafizah Ramli; Muhammad Mun’im Zabidi; Anuar Ahmad; Ivin Amri Musliman (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
This work describes an open source tracking system that determines the location and speed of a vehicle in real-time. The system was inspired by the need to track tourist boats in UNESCO Kilim Karst Geoforest Park, Malaysia. Boats that travel too fast generate wakes that are suspected to cause ecological damage. In this work, geolocation information is provided by Arduino based transponders with Global Positioning System (GPS). Transponders periodically transmit location and speed data using LoRa through a gateway to a cloud server. On the server, open source software components implement a Geographical Information System (GIS) to manage the location and speed data for display and further analysis. The resulting prototype performed the required functions as expected.